Discerning Financial and Investment Epiphanies: Challenges, Inhibitions, and Global Perspectives - What Secrets Does Research Reveal? - Lulaj, Enkeleda (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2025)
The aim of this research was to uncover the secrets related to discerning financial and investment epiphanies through the Challenging Factor of Investments (CHFoI), the Inhibiting Factor of Investments (IFoI), and Demand and Perspective in Investments (DaPiI). It aims to find out how CHFoI is related to IFoI, how IFoI is related to DaPiI, and how IFoI mediates the relationship between CHFoI and DaPiI through direct and indirect effects. Data were collected from owners and investors of 131 companies in different countries (Kosovo, Albania, Montenegro, Belgium, Austria, Germany, United Kingdom, and USA) during the years 2021-2023. Rigorous data analysis methods were used, including exploratory factor analysis (EFA), reliability analysis (Cronbach’s alpha), confirmatory factor analysis (CFA), and structural equation modeling (SEM) using SPSS (64-bit) and AMOS (26.0) software programs. The results revealed three pivotal factors-IFoI, DaPiI, and CHFoI-and their subfactors. highlighting their significance in financial and investment dynamics. Specific influences such as instability in exchange rates, rising production costs, and stability-focused investments were identified. Strong correlations and low p-values indicated robust statistical significance, emphasizing the interconnectedness of IFoI, CHFoI, and DaPiI. However, no significant relationship was found between DaPiI and IFoI. The research findings contribute to the understanding of the complex dynamics of finance and investment and provide transformative insights for refining investment strategies. These insights can guide professionals in the field and support informed decision-making. Future research should delve deeper into the relationships between CHFoI, IFoI and DaPiI to reveal additional discoveries.